(Micro)Mobilidade por patinetes elétricos e o ambiente construído : proposição de um índice de patinetabilidade - Lucas Tadeu Albino de Souza (2021)
Technological advances have introduced new concepts in transport such as smart cities and shared economy. The newest challenge for cities is to understand how the resulting mobility proposals involving electric propulsion, shared (micro)vehicles, and integrated digital platforms can contribute to the emerging sustainable approach that aims to (re)shape (more) dense, diverse, humane and democratic urban spaces. In this sense, the implementation of shared e-scooter programs in Belo Horizonte - as well as in other urban centers around the world, has demanded from the City Officials, Private Initiative and Scientific Community, among other reflections and guidelines, an understanding of how the built environment must be explored and/or (re)adapted to maximize the opportunities offered by the mode and minimize its risks. The objective of the work is, therefore, to propose an E-Scootability Index (IP) – analogous to those of Walkability and Cycling, through which it is possible to assess the quality of the built environment for e-scooter riding. The selection of the IP Indicators was based, mainly, on those of Cycling gathered by Bagno (2019). After selecting those associated with the Cycling and Urban Infrastructure and Urban Design, an Online Survey based on the Likert Scale was applied. For each of the most relevant indicators, according to the perception of those who know Belo Horizonte, weights were obtained through the relative importance, estimated by the Method of Successive Intervals Analysis (Guilford, 1975). The results of the application of the IP in cycling routes in the Centro-Sul and Pampulha Region demonstrate deficiencies in/of the cycling infrastructure for micromode riding, such as, stretches with narrow widths, numerous pavement pathologies, deficient maintenance of bicycle markings and low connectivity / continuity. It is concluded, therefore, that the cycling space, common to micromobility, can produce different levels of comfort and safety for its participants, and it is necessary to proceed with the understanding of the particularities of each micromode, to thus encourage its use and take advantage of the benefits of “smallness”, where it applies.